2020
DOI: 10.15562/bmj.v9i3.2086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral L-Arginine supplementation on intima hyperplasia after Fogarty balloon embolectomy catheterization in New Zealand Rabbit (Oryctolagus cuniculus)

Abstract: Background: Acute limb ischemic is a disease that threatens the viability of the leg with the threat of amputation to death. Fast and accurate diagnosis is essential in the management of this disease, one of the most commonly performed surgical therapies in Indonesia is thromboembolectomy using a Fogarty catheter. Thromboembolectomy with this method is very effective but gives a variety of complications, one the complication is the occurrence of intima hyperplasia which affects the lumen restenosis of the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an experimental study model on rabbits, the development of intimal hyperplasia due to a Fogarty balloon catheter was demonstrated histopathologically. 19 In a case report by Smith et al, a case of progressive intimal hyperplasia developing in the third month after embolectomy was reported. 20 In our study, we identified early re-embolectomy as an independent predictor of amputation development, in both multivariate analysis models.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study model on rabbits, the development of intimal hyperplasia due to a Fogarty balloon catheter was demonstrated histopathologically. 19 In a case report by Smith et al, a case of progressive intimal hyperplasia developing in the third month after embolectomy was reported. 20 In our study, we identified early re-embolectomy as an independent predictor of amputation development, in both multivariate analysis models.…”
Section: Discussionmentioning
confidence: 99%